2021
DOI: 10.3390/plants10122701
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoparticles Inactivate Alfalfa Mosaic Virus Replication and Boost Innate Immunity in Nicotiana glutinosa Plants

Abstract: Plant viral infection is one of the most severe issues in food security globally, resulting in considerable crop production losses. Chitosan is a well-known biocontrol agent against a variety of plant infections. However, research on combatting viral infections is still in its early stages. The current study investigated the antiviral activities (protective, curative, and inactivation) of the prepared chitosan/dextran nanoparticles (CDNPs, 100 µg mL−1) on Nicotiana glutinosa plants. Scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 91 publications
1
13
0
Order By: Relevance
“…The physical barrier created by lignin deposition is more effective at preventing viral infection [ 72 ]. Our results match those of other studies [ 52 , 73 ] that considered the ability of different nanoparticles to increase the activity of plant enzymes in response to ROS. Additionally, ROS can harm the plant’s membrane lipids, proteins, and DNA, leading to symptom development rather than defense or acclimation if the timing and magnitude of ROS accumulation are not tightly controlled by the plant’s antioxidant system [ 74 , 75 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The physical barrier created by lignin deposition is more effective at preventing viral infection [ 72 ]. Our results match those of other studies [ 52 , 73 ] that considered the ability of different nanoparticles to increase the activity of plant enzymes in response to ROS. Additionally, ROS can harm the plant’s membrane lipids, proteins, and DNA, leading to symptom development rather than defense or acclimation if the timing and magnitude of ROS accumulation are not tightly controlled by the plant’s antioxidant system [ 74 , 75 ].…”
Section: Resultssupporting
confidence: 91%
“…In comparison, the shoot and fresh root weight in treatment with standard nanoclay 48 h before PVY inoculation significantly decreased (2.23 g and 0.81 g, respectively) compared with the potato plant control ( Table 4 ). In this context, several previous reports have shown that the foliar application of nanoparticles significantly enhanced plant growth, decreased disease severity, and decreased the accumulation levels of many plant viruses inside plant tissues [ 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Th23 treatment or Th23 + TMV treatment triggered the expression level of PR-1 with significant increases of 385.06% and 203.45%, respectively, when compared with the TMV treatment. Salicylic acid (SA) is a well-known plant signal phytohormone molecule, and its role in plant immune activation has been documented for more than two decades [ 20 , 93 , 94 ]. Furthermore, several studies have shown that PR-1 is an SA marker gene, an important regulator of SAR, and a predictor of early plant defensive response [ 93 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a Nano SPECTROstar spectrophotometer and gel electrophoresis, the quality of the RNA was determined. One µg of total RNA (pretreated with DNase I) from each sample was utilized as a template for cDNA synthesis, as reported previously [ 19 ]. Different primers were used to detect the expression of pathogenesis (PR) and polyphenolic-related genes listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%